Deconstructing Gender Stereotypes in Media: The Transformative Power of Media Literacy (Indian Journal of Mass Communication and Journalism (IJMCJ), 2025)
The stereotypical perception of certain groups or communities has emerged as one of the most serious challenges in our multicultural, globalized society. While globalization has facilitated new economic opportunities and the free flow of resources, technology, ideas, and culture, market-driven consumerism has, on the other hand, narrowed human perspectives by promoting stereotypical projections and perceptions. This poses a significant obstacle to the development of a truly interconnected and inclusive multicultural world. The increasing stereotypical portrayal of men and women by the media remains a critical concern for society, and current trends suggest that such portrayals will persist in the long run. This article is a modest attempt to highlight the various gender stereotypes perpetuated by the media and explore the potential of media literacy in countering these stereotypes. Grounded in a qualitative approach, this study employs a Narrative Literature Review as its research method. The review synthesizes existing literature from multiple research databases, including JSTOR, Google Scholar, ResearchGate, Academia.edu, and CORE.uk, offering a thorough, critical, and objective analysis of the topic. On the one hand, the study provides a comprehensive examination of the portrayal of gender stereotypes across various media platforms; on the other hand, it investigates the transformative potential of media literacy in challenging and counteracting these biased and stereotypical narratives.